Hotel Resort Paropo With Neo Vernacular Approach - Uci Utari; Wahyu Utami (Talenta Publisher, 2020)
Lake Toba is the largest lake in Indonesia, even in Southeast Asia. Lake Toba has excellent potential as a tourism area development in North Sumatra. On the outskirts of Lake Toba, especially Paropo, there are still many who do not have facilities for tourists, the large number of tourists who come to Paropo causes the Paropo area to need supporting facilities such as resort hotels as supporters of North Sumatra tourism development. Resort hotels are hotels located in tourist attractions, such as mountains, beaches, and lakes. The design of the Paropo resort hotel applies the Neo vernacular architectural concept. The problem with this design is